A Novel Engine Mount with Semi-Active Dry Friction Damping. (2006) - Lorenz, M.; Heimann, B.; Härtel, V.
Abstract : In this paper the authors present a semi-active engine mount with a controllable friction damper. The normal force of the friction contact is applied by an electromagnetic actuator and can be varied dynamically. The nonlinear current-force-relation of the actuator is linearized. To account for wear and assembly tolerances, an initialization method is developed, that is based on indirect measurement of the actuators inductance. The friction contact is made up of industrial friction pads and a friction rod of steel. The friction model used is suitable especially for small oscillations of the friction damper. The control policy imitates viscous damping forces that exert a minimum of harmonics. Damping is activated only when necessary. Finally the friction mount is compared to the original mount in a row of test rack experiments and also in the car.